A STUDY ON INVOLVEMENT OF METAL-BINDING PROTEIN(S) FOR THE BIOSORPTION OF SOME SELECTED HEAVY METALS - Sarkar, Diptendu; Paul, Goutam (JOURNAL OF ADVANCES IN BIOLOGY, 2014)
The present research finding have shown that extracellular protein(s) of growing cells of Pseudomonas aeruginosa DSGPM4 strain are responsible for giving withstand power in presence of toxic heavy metals. To study the role of cadmium, nickel and copper resistance, a preliminary test was done by treating the cells with different concentrations of proteinase K. To perform the test highly resistant isolates DSGPM4 was inoculated in nutrient broth and incubated overnight at 37°C. Reaction tubes were prepared by adding overnight cultures in two different concentrations of proteinase K i.e. 1 mg/ml and 2 mg/ml in the ratio of 1:1 and incubated for 2 hours at 37°C. After incubation, 20 ml of each sample was spread over selective plates containing two different concentrations of PbClâ‚‚ and NiCl2 and CuCl2 i.e., 1mM and 2 mM in growth medium (1x A) as well as on control plates. Control plates were prepared by adding 1 mg/ml (C1), and 2 mg/ml (C2) of proteinase K whereas, other control plates containing 2mM of PbCl‚‚ (C3) and 2mM of NiCl2 (C4) and CuCl2 (C5) salts but no proteinase K.To find out whether the extracellular protein has any role in metal resistance, preliminary test was conducted by treating the plasmid bearing isolate (DSGPM4) and a control DSGPM4 with protease. This study reports the accumulation of some heavy metals (Cu, Ni and Pb) by growing cells of Pseudomonas aeruginosa DSGPM4 strain and the purification and molecular characterization of related heavy metal binding proteins.